2006
DOI: 10.1021/ol053033y
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented SnCl2-Mediated Cyclization of Nitro Arenes via N−N Bond Formation

Abstract: [reaction: see text] A mild, efficient, one-pot protocol for the cyclization of nitro-aryl substrates using SnCl(2) has been described. The mechanistic course of the reaction suggests the involvement of a hydroxylamine intermediate leading to an intramolecular cyclization via N-N bond formation. The versatility of the methodology has been demonstrated by using two nitro-aryl substrates derived from dihydroisoquinolines and dihydro-beta-carbolines. The intramolecular cyclization led to the formation of indazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…The latter is isolobal to a phosphine and acts as a ligand. However, in the present case it should be noted that SnCl 2 reduces nitroarenes under much milder conditions than those employed for the catalytic reaction and that an over‐stoichiometric amount of SnCl 2 has even been employed to promote the reductive cyclization of N‐ (2‐nitroarylidene)amines to 2 H‐ indazoles in the absence of any metal catalyst . Since the amount of SnCl 2 is not negligible (0.5 equiv.…”
Section: Synthesis Of N‐heterocycles By Intra‐molecular Cyclization Rmentioning
confidence: 86%
See 1 more Smart Citation
“…The latter is isolobal to a phosphine and acts as a ligand. However, in the present case it should be noted that SnCl 2 reduces nitroarenes under much milder conditions than those employed for the catalytic reaction and that an over‐stoichiometric amount of SnCl 2 has even been employed to promote the reductive cyclization of N‐ (2‐nitroarylidene)amines to 2 H‐ indazoles in the absence of any metal catalyst . Since the amount of SnCl 2 is not negligible (0.5 equiv.…”
Section: Synthesis Of N‐heterocycles By Intra‐molecular Cyclization Rmentioning
confidence: 86%
“…However, in the present case it should be noted that SnCl 2 reduces nitroarenes under much milder conditions than those employed for the catalytic reaction [130][131][132] and that an over-stoichiometric amount of SnCl 2 has even been employed to promote the reductive cyclization of N-(2-nitroarylidene)amines to 2H-indazoles in the absence of any metal catalyst. [133] Since the amount of SnCl 2 is not negligible (0.5 equiv. with respect to the nitroarene) in the cited system, its role as a direct reductant cannot be dismissed.…”
Section: Synthesis Of Other 5-membered N-heterocyclesmentioning
confidence: 99%
“…Another example of N-O bond cleavage, in this case involving nitro group reduction, was disclosed by Kundu and co-workers in 2006 (Scheme 5). 19 In the presence of TsCl, the hydroxylamine M2 formed by reduction of the nitro group undergoes intramolecular cyclization to afford pyrazoles 6 in 89-91% yield.…”
Section: Scheme 4 Cyclization Of Oximes By Intramolecular Nucleophilimentioning
confidence: 99%
“…Under review of literatures, it was found that nitrogen‐containing heterocyclic compounds could be prepared by direct reduction of nitro compounds . Inspired by this approach, we have reported an efficient and simple method for the synthesis of pyrazolo[3,4‐ a ]acridin‐10‐one and pyrazolo[4,3‐ a ]acridin‐10‐one derivatives form 5‐nitro‐1 H ‐indazole and 6‐nitro‐1 H ‐indazole .…”
Section: Introductionmentioning
confidence: 99%